ANALYSIS OF DISTORTIONS IN HIGH-FREQUENCY PULSE ACOUSTIC SIGNALS WITH LINEAR FREQUENCY MODULATION IN A HYDROACOUSTIC COMMUNICATION CHANNELS - V. E. Denisov (Российский технологический журнал)
The article deals with the distortion of high-frequency acoustic pulses with linear frequency modulation (LFM) in a hydroacoustic communication channel, which is caused by uneven frequency attenuation characteristics of the marine environment. The paper considers pulses with rectangular, sinusoidal and "raised cosine" type envelopes.